Examining the Determinants of Continuance Intention to Use Mobile Payment Service - Ihsan Atmaji; Viany Utami Tjhin (Journal of Information System and Informatics, 2022)
Innovation in finance and advances in payment sytems are very important to boost remittances and encourage the successful development of electronic businesses around the world. Thus, many leading companies use mobile payment services to improve the customer experience of their customers. This study aims to identify the factors that influence consumers to continue using mobile payment in Indonesia. Several influencing factors include Service Quality, Perceived Ease of Use, Security, Perceived Usefulness, and Trust. This research was conducted in Madiun City, one of the big cities in Indonesia, with a total of 176 respondents. The study results can help mobile payment companies understand factors that are relevant to increasing volume usage in the context of merchants. The findings of this research is Continuance Intention influenced by Trust. Trust is significantly influenced by the independent variables such as Service Quality, Perceived Ease of Use, Security, and Perceived Usefulness. However, perceived risk has no significant effect on continuance intention. Therefore, mobile Payment service providers should be able to implement action plans related to the quality of their services, user experience to customers, security of an application, and the functions and features implemented by a Mobile Payment. Hopefully those things will generate trust in customers to continue to use Mobile Payment services.